A systematic review of anticoagulants evaluating efficacy and safety in thromboembolic disease - Turkistani, Yassir A.; Alsaedi, Emad; Alsawadi, Bader H.; Almasabi, Fawaz M.; Jeddo, Fatmah A.; Alrehaili, Renad K.; Alrehaily, Rahaf S.; Almarwani, Mohammed N.; Beitar, Feras S.; Alahmadi, Turki A.; Alrehaili, Yara M.; Almutairi, Aljuri H.; et al. (International Journal Of Community Medicine And Public Health, 2026)
Venous thromboembolism (VTE) is a major global source of morbidity and mortality. Oral anticoagulants have become a safer and more effective alternative to conventional anticoagulants, such as heparin and warfarin, which have been the cornerstone of treatment. They have shown comparable efficacy with fewer significant bleeding episodes. This study investigated the efficacy and safety of oral anticoagulants in comparison with other conventional anticoagulant therapies in patients with venous thromboembolism. A systematic review was conducted where data were obtained from PubMed, Scopus, Google Scholar, and Clinicaltrials.gov, covering the period from January 2020 to July 2025. Study selection was conducted in accordance with PRISMA guidelines and illustrated using a PRISMA flowchart. Eligible studies included randomized clinical trials, cohort studies, and observational studies that compared direct oral anticoagulants (DOACs) with conventional or other anticoagulant therapies. Data extraction was performed independently by two reviewers (EA), who identified relevant studies and extracted information on study characteristics, outcomes, and efficacy from the included articles. It was found that VTE is effectively managed with prolonged anticoagulation therapy. Research indicates that a minimum duration of three to six months of oral anticoagulant use significantly reduces the risk of recurrent VTE and is associated with fewer major bleeding events. Among the available options, a 20 mg dose of rivaroxaban has been shown to offer the highest efficacy. In contrast, monotherapy with agents such as vitamin K antagonists, aspirin, or warfarin is generally less effective, whereas combination therapy with oral anticoagulants provides improved outcomes. It is concluded that for patients with venous thromboembolism, direct oral anticoagulants are a safer and more efficient therapeutic option than vitamin K antagonists and traditional anticoagulation treatments.